EVALUASI INTENSITAS PENYAKIT KUNING TERHADAP HASIL CABAI KERITING (Capsicum annuum L. var. Acuminatum) PASCA LETUSAN GUNUNG MERAPI 2010 - , FITRIA NUGRAHENI SUKMAWATI; , Dr. Ir. Endang Sulistyaningsih, M. Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Yellow disease caused by pepper yellow leaf curl virus (PYLCV) is one of the most important virus in tropic and sub tropic countries. This virus was transmitted by Bemisia tabaci and caused yield losses in pepper. West side mountain Merapi is a center of pepper plantation areas but all areas are infected by pepper yellow leaf curl virus for long. Therefore, that areas are identified as endemic areas of Pepper yellow leaf curl virus. After Merapi Eruption 2010 in that endemic area the farmers reported that yellow disease intensity on pepper was decline. The aim of research was to obtain data of yellow disease intensity, Bemisia tabaci population, and yield of pepper around west side mountain Merapi after eruption in 2010. The research was conducted in west side mountain Merapi, Magelang, Central Java from October 2011 - June 2012. The intencity yellow disease data before Merapi eruption obtained from a previous research conducted at the location with the same hight as this research. The experimental was Nested in three levels of altitude (550 masl, 400 masl, and 250 masl) and using three blocks. In each altitude its blocks there are two different plant conditions (symptom and no shown symptom) with three samples. Data was collected for morphological, sitological, and molekular characters of pepper plant with yellow disease. Moreover, data of pepper plant management were collected using quetionaire for 10 farmers for each altitude. All data were statistically analyzed using the analisys of variance (ANOVA), followed by Duncan Multiple Range Test (DMRT) to determine the significant differences among treatment means. T test was be used to compare symptom and no shown symptom and to compare top and buttom of a leaf parameters. Chi Square was used to determine the significant differences cultivated among farmers in all locations. The results showed that altitude 550 masl and 250 masl of lower Bemisia tabaci population compared to that of in altitude on 400 masl. After Merapi mount eruption 2010, the yellow disease intencity on 550 masl, 400 masl, and 250 masl were decreased 75,36 %, 41,52 %, and 47,8 % respectively. The yield on 550 masl was highest than others (6,26 ton/ha). The difference symptom and no shown symptom plant was detected on all variables. Cropping pattern, watering frequency, and weed control frequency were different in all locations.